The Need for Love and Belongingness in - Khilfanailah Risvania Olga (Fakultas Ilmu Budaya, 2026)
Love is not only able to understand, but also able to respect and trust. This research will discuss how the author depicts love and belongingness in the novel, as well as how it connects to the Jane Austen psychological background to understand the creative process in creating the fictional character in the novel.The goal of this study is to examine Jane Austen's Sense and Sensibility from the standpoint of psychological approach, with an emphasis on how the protagonists satisfy their needs for love and belonging and how these needs influence the plot and characters. The research method used a qualitative method. The results of the study show the fulfillment of the need for love and belongingness in the characters Elinor and Marianne in Family, Society, and Bridegroom. The results also show the existence of two different dichotomies, namely power which is described as self-control and emotional management. Meanwhile, feminine authority is shown in the excessive criticism emphasized on female characters like Lucy Steele compared to male characters like Willoughby. Behind the struggle of the Dahwood sisters in finding true love, there is tension rather than calm depicted in power and feminine authority.
Finalisasi Maya_05 Agustus 2026
Keywords: Sense and Sensibility; Jane Austen; Psychological Approach; Love and Belongingness